2003
DOI: 10.4141/a02-020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage time and exogenous xylanase supplementation of new season wheats on the performance of young male pigs

Abstract: Cadogan, D. J., Choct, M. and Campbell, R. G. 2003. Effects of storage time and exogenous xylanase supplementation of new season wheats on the performance of young male pigs. Can. J. Anim. Sci. 83: 105-112. A series of experiments was conducted to investigate the influence of new season wheats on pig growth performance. Experiments were carried out on 10 different wheats at the time of harvest and 10 mo post-harvest. At harvest wheat, at a 65% level in the steam-pelleted diets, influenced (P < 0.01) feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In a study of Gill et al (2000) with weaned piglets fed a wheat-based diet (706 g wheat/kg diet as-fed), supplementation of an enzyme cocktail, including xylanase, amylase, ␤-glucanase and pectinase, resulted in a significant improvement in feed conversion rate compared to the unsupplemented diets. This is in accordance with the results of a study by Cadogan et al (2003), where supplementing xylanase to a wheat-based diet (650 g wheat/kg diet as-fed) increased daily gain and feed intake and tended to improve feed conversion rate. In nursery pigs, however, enzyme supplementation to a wheat-based diet (530 g wheat/kg diet on average) did not affect growth performance, eventually due to the lower inclusion level of wheat in the diets (Mavromichalis et al, 2000).…”
Section: Enzyme Supplementation In Wheat and Wheat By-product Based Dsupporting
confidence: 93%
“…In a study of Gill et al (2000) with weaned piglets fed a wheat-based diet (706 g wheat/kg diet as-fed), supplementation of an enzyme cocktail, including xylanase, amylase, ␤-glucanase and pectinase, resulted in a significant improvement in feed conversion rate compared to the unsupplemented diets. This is in accordance with the results of a study by Cadogan et al (2003), where supplementing xylanase to a wheat-based diet (650 g wheat/kg diet as-fed) increased daily gain and feed intake and tended to improve feed conversion rate. In nursery pigs, however, enzyme supplementation to a wheat-based diet (530 g wheat/kg diet on average) did not affect growth performance, eventually due to the lower inclusion level of wheat in the diets (Mavromichalis et al, 2000).…”
Section: Enzyme Supplementation In Wheat and Wheat By-product Based Dsupporting
confidence: 93%
“…Several studies have reported improved performance of pigs when xylanase or other glycanases were used in diets with high levels of NSP (Li et al 1996;Cadogan et al 2003;Omogbenigun et al 2003). Barrera et al (2004) reported that xylanase at the rate of 11 000 U kg -1 supplemented to diets in which wheat made up about 98% of the diet led to improvement in average daily gain of 20.5-kg pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Xylanase, a glycosidase enzyme, hydrolyzes the arabinoxylan structure, thus increasing the digestion of NSP (Härkönen et al 1995), the release of bound protein (Tervilä-Wilo et al 1996), and the reduction in digesta viscosity (Choct et al 1999), with consequent enhancement of livestock performance. The use of xylanase in wheat-based diet fed to young pigs resulted in improved daily gain and feed intake (Cadogan et al 2003), increased total tract digestibility of nutrients (Omogbenigun et al 2003) …”
mentioning
confidence: 99%
“…Phytase supplementation of P-deficient diets resulted in improved growth performance of pigs (Nasi, 1990;Cromwell et al, 1993;Han et al, 1997) and improved P and Ca utilization (Nasi, 1990;Adeola, 1995). Adding carbohydrases to a wheat-based diet fed to young pigs resulted in improved ADG and ADFI (Cadogan et al, 2003), increased total tract digestibility of DM and N (Mavromichalis et al, 2000), and improved energy digestibility in wheat-soybean meal (SBM) diet (Li et al, 1996). Feedstuffs are heterogeneous in composition; hence to derive maximum benefits from enzyme supplementation, the use of cocktail of enzymes with different activities that target the different chemical components might be more beneficial than using an enzyme with a single activity.…”
Section: Introductionmentioning
confidence: 99%